ORGANIZATION OF STUDENTS’ INDEPENDENT WORK IN STUDYING PHYSICS BASED ON DISTANCE LEARNING TECHNOLOGY IN LMS MOODLE - Viktor Yu. Shurygin; Lyubov A. Krasnova (Образование и наука)
The aim of the article is to justify and substantiate the importance and usefulness of e-learning courses on the platform LMS MOODLE in the context of improving the quality of independent work of students in the study of high school physics course.Methods. Developed online courses in physics in LMS MOODLE based on the analysis of scientific publications and research, observations, lessons learned and results of educational activities are presented; the peculiarities of their application in terms of improving the effectiveness of different types of independent activity of students of high school are identified.Results. A brief analysis of the main trends of distance learning is given; the experience of the development and application of electronic educational courses on the main sections of the course of physics in the Physics and Mathematics Department at the Institute of Elabuga Kazan (Volga) Federal University is described. It is concluded that the use of e-learning in the educational process enhances the effectiveness of different types of independent activity of students, self-development, and the formation of their professional competence.Scientific novelty. The notion of electronic educational courses and its place in the system of blended learning are clarified. The key features and opportunities for intensification of educational process and enhancing students’ independent work are highlighted.Practical significance. Outlined in the article the possibilities and potential of the spacers on a platform LMS MOODLE, as well as the features of their application can determine ways to optimize and streamline the learning process, improvement of methods and tools for the repose of information, monitoring, diagnosis of different types of self-employment. Presented experience of independent work of students in studying physics course based on e-learning courses can be used in various educational institutions of higher education.